The Juridical Analysis Of Medical Malpractice Actions Carried Out By Ophthalmologist - Ari Andayani; Agus Kurniawan (Jurnal Jurisprudence, 2023)
ABSTRACT / ABSTRAK Purpose of the Study: This research aimed to analyze legal considerations in malpractice cases carried out by ophthalmologists and analyze the differences between medical risk and medical malpractice Methodology: This research is normative legal research using the statute approach and case approach of medical malpractice cases. The research object discussed is the Supreme Court Judgment Number 277/PDT/2020/PT SBY and Supreme Court Judgment Number 338 K/Pdt/2020. The analysis technique implemented descriptive qualitative analysis. Results: The results of the research discovered that the judge's consideration in issuing nt in malpractice case by an ophthalmologist was inconsistent and defied the applicable laws and regulations, in which Articles 359 and 360 of the Criminal Code the judge should have imprisoned to the perpetrator. Apart from that, the judgment 277/PDT /2020/PT SBY is included in the medical malpractice action which is shown by the damages given to the patient and an apology from the doctor. Applications of this study: Research suggests the conformity of judgment with laws and punishment that should be given to doctors who committed medical malpractice from the proof and applicable laws and regulations. Novelty/Originality of this study: The study analyzed the judgments of medical malpractice cases through 6 court processes. Keywords: Medical Malpractice, Liability, Criminal Law   Abstrak / Abstrak  Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis pertimbangan hukum dalam kasus penyalahgunaan yang dilakukan oleh dokter mata dan untuk menganalisa perbedaan antara risiko medis dan penyimpangan medis Metodologi: Penelitian ini adalah penelitian hukum normatif menggunakan pendekatan hukum dan pendekatan kasus kasus kasus penyalahgunaan medis. Objek penelitian yang dibahas adalah Keputusan Mahkamah Agung Nomor 277/PDT/2020/PT SBY dan Keputusan Pengadilan Tinggi Nomor 338 K/Pdt/2020. Teknik analisis yang digunakan adalah analisis deskriptif kualitatif. Hasil penelitian menemukan bahwa pertimbangan hakim dalam mengeluarkan nt dalam kasus penyalahgunaan oleh seorang dokter mata tidak konsisten dan menantang hukum dan peraturan yang berlaku, di mana Pasal 359 dan 360 dari Kode Kriminal hakim harus menahan pelaku. Selain itu, putusan 277/PDT/2020/PT SBY termasuk dalam tindakan penyalahgunaan medis yang ditunjukkan dengan kerusakan yang dialami pasien dan maaf dari dokter. Aplikasi dari penelitian ini: Penelitian menunjukkan kesesuaian penilaian dengan hukum dan hukuman yang harus diberikan kepada dokter yang melakukan penyalahgunaan medis dari bukti dan hukum dan peraturan yang berlaku Novelty/Originality of this study: Studi ini menganalisis penilaian kasus penyalahgunaan medis melalui 6 proses pengadilan. Kata Kunci: Penyalahgunaan Medis, Tanggung Jawab, Hukum pidana